2021
DOI: 10.1007/s40544-020-0476-y
|View full text |Cite
|
Sign up to set email alerts
|

Tribological properties of multilayer tetrahedral amorphous carbon coatings deposited by filtered cathodic vacuum arc deposition

Abstract: Tetrahedral amorphous carbon (ta-C) has emerged as an excellent coating material for improving the reliability of application components under high normal loads. Herein, we present the results of our investigations regarding the mechanical and tribological properties of a 2-µm-thick multilayer ta-C coating on high-speed steel substrates. Multilayers composed of alternating soft and hard layers are fabricated using filtered a cathodic vacuum arc with alternating substrate bias voltages (0 and 100 V or 0 and 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Diamond-like carbon (DLC) films are well known for their superior mechanical properties, chemical inertness, and especially excellent self-lubricating performance [1,2], and they have been widely accepted as one of the most promising self-lubricating protective layers in mechanical systems [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Recently, it was reported that sufficient hydrogen incorporation can make DLC films capable of achieving near-frictionless sliding state with an extremely low friction coefficient (below 0.01) and negligible wear when rubbed in dry inert atmosphere such as nitrogen, carbon dioxide, and argon [3,[20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Diamond-like carbon (DLC) films are well known for their superior mechanical properties, chemical inertness, and especially excellent self-lubricating performance [1,2], and they have been widely accepted as one of the most promising self-lubricating protective layers in mechanical systems [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Recently, it was reported that sufficient hydrogen incorporation can make DLC films capable of achieving near-frictionless sliding state with an extremely low friction coefficient (below 0.01) and negligible wear when rubbed in dry inert atmosphere such as nitrogen, carbon dioxide, and argon [3,[20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In light of the design and construction for multilayered DLC films, it is of great significance to realize the synergistic combination of different properties from the individual sublayers and to enhance the load bearing capacities without sacrificing its superlubricious properties. 31,32 Theoretical studies indicated an assessment method for estimating the ability of the load bearing capacity under the heavy-load operating conditions, which was related to the stress field adaptation relationship between the film and substrate of the multilayer films. 33,34 films, a concept of the stress relaxation caused by cracks, warps, and deformations at the interface of the substrate and the films and closely associated with the mismatched strain energy was brought forward to evaluate the load bearing capacity of the multilayered films.…”
Section: Introductionmentioning
confidence: 99%
“…This excellent tribological performance strongly depended on the effect of H 2 gas lubrication and the strong H-passivation effect and the transfer film formed at the contact interfaces, which directly resulted in a reduction of the surface adhesive force. In light of the design and construction for multilayered DLC films, it is of great significance to realize the synergistic combination of different properties from the individual sublayers and to enhance the load bearing capacities without sacrificing its superlubricious properties. , Theoretical studies indicated an assessment method for estimating the ability of the load bearing capacity under the heavy-load operating conditions, which was related to the stress field adaptation relationship between the film and substrate of the multilayer films. , Based on the WC/C nanocomposite films, a concept of the stress relaxation caused by cracks, warps, and deformations at the interface of the substrate and the films and closely associated with the mismatched strain energy was brought forward to evaluate the load bearing capacity of the multilayered films . Under the ultrahigh contact stress conditions, the proposed threshold value of the mismatched strain energy of interfaces between the films and the substrate will be a quantitative evaluation way to understand the limitations of stress resistance of the well-designed multilayered DLC films.…”
Section: Introductionmentioning
confidence: 99%
“…An example is aluminum oxide, which exhibits lower wear rates, as well as a more constant friction behavior, when compared to silicon nitride and steel [ 11 ]. Multilayering soft and hard ta-C coatings may be another way to improve wear performance and mechanical properties in general [ 12 ].…”
Section: Introductionmentioning
confidence: 99%